Bibliometric analysis of swimming learning models for students (2002-2024): Trends, gaps, and future directions - Arhesa, Sandra; Ma'mun, Amung; Lumba, Andreas J. F.; Blegur, Jusuf; Calunsag, Buena D. (Universitas Negeri Yogyakarta, 2025)
Drowning during swimming has become a significant public health concern that urged the World Health Organization to call for all school-aged children to be taught basic swimming skills, water safety, and rescue techniques. In this teaching, efficiency shall be obtained with the help of an effective learning model. This study will investigate the publication trends of research about swimming learning models carried out for students during the last 22 years, from 2002 until 2024, using the data from the Scopus database. The search was carried out on August 7, 2024, by title, abstract, and keywords, using the sets of words